FAKTOR-FAKTOR YANG BERPENGARUH PADA KEPUASAN PEMAKAI SISTEM INFORMASI AKUNTANSI LEMBAGA PERKREDITAN DESA DI KECAMATAN MENGWI - Surya, Anak Agung Made; Sadha Suardikha, I Made (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
This study aims to determine "Factors Influencing Satisfaction User Accounting Information Systems at LPD in District Mengwi". This research was done on the LPD in District Mengwi. Samples in this study of 61 respondents to the sampling technique used was purposive sampling. The data collection method used is the method of questionnaires. The data analysis technique used is the technique of multiple linear regression analysis. Based on the results of research by distributing questionnaires to 61 respondents, it can be concluded that the factors of training and education, support of top management, information systems development, user involvement in the development of the system positively affects user satisfaction SIA. This shows if the user SIA wants to achieve satisfaction with the system used, it should be noted the factors that affect it..
Keywords: user satisfaction, training and education, support of management, systems development, the involvement of users